2022
DOI: 10.1037/spq0000473
|View full text |Cite
|
Sign up to set email alerts
|

Dimensions of family–school partnerships for autistic children: Context and congruence.

Abstract: Family-school partnerships are crucial for promoting positive outcomes and serving as a protective factor for children at-risk for poor school outcomes (Christenson & Sheridan, 2001). This may be particularly important for autistic children, who are at increased developmental risk . However, little research has examined variables related to dimensions of these partnerships for parents and teachers of autistic children. The present study examined family socioeconomic resources in relation to two dimensions of f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…This research has focused on the perception of teachers, school management teams and educational inspection, therefore, in future studies it would be advisable to also collect the voices of students and families, particularly minority and culturally diverse families (Miller, 2019;Santiago et al, 2021) to reach a global view of the entire educational community regarding family-school-community collaboration.…”
Section: Discussionmentioning
confidence: 99%
“…This research has focused on the perception of teachers, school management teams and educational inspection, therefore, in future studies it would be advisable to also collect the voices of students and families, particularly minority and culturally diverse families (Miller, 2019;Santiago et al, 2021) to reach a global view of the entire educational community regarding family-school-community collaboration.…”
Section: Discussionmentioning
confidence: 99%
“…An initial step for considering this broad construct within family–school partnership practice is to incorporate family appraisal of these factors. For example, one study found that among parents of autistic youth, parental appraisal of higher financial resources was associated with higher family involvement, whereas externally measurable dimensions of SES (e.g., income, employment) were not associated (Santiago et al, 2022). Understanding how families view their context can inform help schools understand families’ experience of stress, mental health, and their children, which is critical for partnering with families.…”
Section: Discussionmentioning
confidence: 99%
“…This was included in analyses as a four-level categorical variable. Although household income has commonly been used as the variable measuring family financial resources, recent research has highlighted the value of examining subjective indicators of financial resources rather than objective indicators (Santiago et al, 2022).…”
Section: Ses Variablesmentioning
confidence: 99%
See 1 more Smart Citation